Indonesia Sebagai Negara Kepulauan - Sunaryo, Thomas (UI Scholars Hub, 2019)
Indonesia's persistent struggle through the Juanda declaration has succeeded in obtaining juridical recognition regarding the boundary of Indonesia as an intact archipelago in the UN III Convention on the International Sea Law (UNCLOS) 1982, although the United States as a superpower country does not admit it. Nevertheless, in International forum, The Unitary State The Republic of Indonesia (NKRI) has had territorial sovereignty and additional zones, Exclusive Economic Zone (ZEE) in a national sphere with all its natural wealth content belonging to the nation in the dimension of Nusantara. This paper intends to show that the Republic of Indonesia ia an arcipelagic country characterized by an archipelago with territory and rights stipulated in law.